2003
DOI: 10.1124/jpet.103.058602
|View full text |Cite
|
Sign up to set email alerts
|

Activation of G-Proteins by Morphine and Codeine Congeners: Insights to the Relevance of O- and N-Demethylated Metabolites at μ- and δ-Opioid Receptors

Abstract: Phenotypic differences in analgesic sensitivity to codeine (3-methoxymorphine) results from polymorphisms in cytochrome P450 -2D6, which catalyzes O-demethylation of codeine to morphine. However, O-demethylation reportedly is not required for analgesic activity of the 7,8-saturated codeine congeners dihydrocodeine, hydrocodone, and oxycodone. This study determined the potency and efficacy of these compounds and their demethylated derivatives to stimulate -and ␦-opioid receptor-mediated G-protein activation usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…The m-agonists tested in this study were selected because they vary along a continuum of efficacy to activate G protein signaling pathways coupled to m-receptors (Selley et al, 1997(Selley et al, , 1998Thompson et al, 2004). Despite these differences in efficacy at the receptor level, all six m-agonists were fully effective to block both acid-stimulated stretching and acid-induced depression of ICSS.…”
Section: Effects Of M-opioid Receptor Ligands On Icssmentioning
confidence: 99%
See 1 more Smart Citation
“…The m-agonists tested in this study were selected because they vary along a continuum of efficacy to activate G protein signaling pathways coupled to m-receptors (Selley et al, 1997(Selley et al, , 1998Thompson et al, 2004). Despite these differences in efficacy at the receptor level, all six m-agonists were fully effective to block both acid-stimulated stretching and acid-induced depression of ICSS.…”
Section: Effects Of M-opioid Receptor Ligands On Icssmentioning
confidence: 99%
“…First, a relatively low-intensity noxious stimulus was used (intraperitoneal administration of 1.8% lactic acid in a volume of 1.0 ml/kg), and antinociception was assessed for a range of m-agonists that vary in their relative efficacies at m-receptors. Specifically, effects were examined for methadone, fentanyl, morphine, hydrocodone, buprenorphine, and nalbuphine [listed in order from highest to lowest efficacy as determined by in vitro functional assays of agonist-stimulated 59-O-(3-thiotriphosphate) binding] (Selley et al, 1997(Selley et al, , 1998Thompson et al, 2004). We predicted that, consistent with their clinical effectiveness (Brunton et al, 2011), all m-opioid receptor agonists would block acid effects in both assays.…”
Section: Introductionmentioning
confidence: 99%
“…For these experiments, a CHO cell line engineered to express relatively low levels of the MOR (0.4 pmol per mg of membrane protein was used), 21 so that NAP and NAQ would act as pure antagonists and readily allow determination of parallel rightward shifts of the DAMGO curve. This MOR expression level was similar to a previously reported MOR B max values (0.2À0.4 pmol/mg) from multiple regions of mouse brain.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro norhydrocodone has been shown to be moderately lower in potency, with similar efficacy, to hydrocodone at mand d-opioid receptors (Thompson et al, 2004). While binding studies and in vitro pharmacodynamic data raise the possibility that norhydrocodone might possess in vivo activity and contribute to the opioid receptor-mediated effects of hydrocodone, to our knowledge, the in vivo activity of norhydrocodone has not been thoroughly examined.…”
Section: Discussionmentioning
confidence: 95%
“…While norhydrocodone has been suggested to be an inactive metabolite (Smith, 2009), one in vitro study examining Gprotein activation by N-demethylated codeine congeners compared to the parent molecules demonstrated that norhydrocodone had lower potency but similar efficacy as hydrocodone for m-and d-opioid receptor-mediated G-protein activation (Thompson et al, 2004). Since these data indicate that norhydrocodone activates opioid receptor signaling and, as noted above, is a major metabolite of hydrocodone, we hypothesized that norhydrocodone may possess in vivo activity and might contribute to the pharmacodynamics of hydrocodone.…”
Section: Introductionmentioning
confidence: 99%